(untitled) (Saúde Ética & Justiça, 2013)
Highway Safety not only involves Human Rights but also, and mainly, the duty of all the participants in road traffi c. Each citizen, as a member of the phenomenon of traffi c and co-responsible for the safety of others, needs to know the effects that alcohol can cause on the human body and must respect the restrictive period that has been stipulated for everyone who has drunk and, after the alcoholic detoxifi cation phase, intends to drive a motor vehicle without violating safety rules and in compliance with Road Safety, knowing that the blood alcohol content BAC is zero. This paper has sought to establish the time necessary, for a person who has ingested a determined quantity of an alcoholic drink, to undergo ethyl-oxidation so that only afterwards, she/he can safely drive a vehicle on the highway.